Outdoor Education in Promoting Nature Appreciation: A Survey through Activity Enjoyment among Physical Education Students in a Public University - Mohamed, Mawarni; Alpandi, Siti Nurfatihah; Kamal, Azlan Ahmad; Mohamed, Ani Mazlina Dewi; Azwan, Zaharul; Rahman, Zarizi Abd; Fariduddin, M. Nur; Zulkifli, A. Fahim (ACPES (ASEAN Council of Physical Education and Sport) in cooperation with Universitas Negeri Semarang (UNNES), 2021)
Outdoor Education (OE) is usually associated with challenging activities and developing skills among students. It also teaches learning through the interaction with the nature world which helps to educate for environmental appreciation. Is the frequency of involvement can determine the appreciation among its participants? So, the objectives of this study are to identify the involvement of outdoor activities, its enjoyment of participation and its relationship with nature appreciation among undergraduate students in a higher learning institution in Malaysia. One hundred and sixty-nine (n=169) students who participated in this study were from a Physical and Health Education Program. Results from the study indicated high levels of participation with much pleasure from diverse outdoor activities in water and land based. Pearson’s correlation analysis was performed between each type of water and land-based activity with nature appreciation. Analyses were found to have significant relation of several activities with nature appreciation. Findings indicated a significant but weak relationship between the overall activities and nature appreciation among the students. It was suggested that integrating together new area of studies related to mother nature should be incorporated during the activities.